Implementasi Pembelajaran Matematika Realistik dalam Menganalisis Kemampuan Penalaran Matematis Siswa pada Materi Satuan Debit - Hewen, Selfiana Bura; Towe, Mariana Marta (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to (1) describe the learning of unit debit with PMR approach and (2) describe the reasoning ability of grade V students on unit debit material. This research was conducted at SDK Lamawalang on April 20, 2024. The subjects in this study were fifth grade students of SDK Lamawalang. The type of research used is descriptive qualitative research, where researchers describe learning practices using PMR models and students' mathematical reasoning abilities after the learning process.  Data analysis techniques used include data collection, data reduction, data presentation, and verification/conclusion. The results showed that, (1) the steps of learning unit debit material with PMR model are: (a) understanding contextual problems, (b) solving problems, (c) comparing and discussing answers, (e) drawing conclusions, (2) based on indicators of mathematical reasoning ability, (a) making conjectures, (b) performing mathematical manipulations, (c) compiling evidence, providing reasons/evidence for the correctness of the solution, and (d) drawing conclusions from a statement, obtained for problem I, 20 students can achieve 1-4 indicators of mathematical reasoning, 1 student can achieve 1-3 indicators of mathematical reasoning. For problem 2, 18 students can achieve 1-4 indicators of mathematical reasoning, while 3 students can achieve 1-2 indicators of mathematical reasoning.